2012
DOI: 10.1111/j.1365-2893.2012.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus wild‐type and rtN236T populations show similar early HBV DNA decline in adefovir refractory patients on a tenofovir‐based regimen

Abstract: Hepatitis B virus (HBV) pol/RT mutations that confer clinical resistance to tenofovir disoproxil fumarate (TDF) have not been detected to date. In vitro, the rtN236T adefovir dipivoxil (ADV)-associated resistance mutation confers low-level cross-resistance to tenofovir: 3- to 13-fold changes in EC(50) from wild type. This study evaluated the clinical response of rtN236T mutant viruses by comparing their early viral load decay kinetics to wild-type viruses in chronic HBV monoinfected patients harbouring rtN236T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…Several studies have already reported that TDF therapy exhibited satisfactory virological and biochemical responses in LMV‐resistant patients. However, clinical data regarding its efficacy in ADV and multiple NA resistance are quite limited . Most importantly, there is no clinical study conducted in Chinese CHB patients, which consists of the majority of the HBV‐infected population in the world.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already reported that TDF therapy exhibited satisfactory virological and biochemical responses in LMV‐resistant patients. However, clinical data regarding its efficacy in ADV and multiple NA resistance are quite limited . Most importantly, there is no clinical study conducted in Chinese CHB patients, which consists of the majority of the HBV‐infected population in the world.…”
Section: Discussionmentioning
confidence: 99%
“…For patients on TDF shown to harbor the rtN236T mutation by population sequencing, the rtN236T mutant percentage was determined with MultiCode RTx allele‐specific PCR modified for HBV rtN236T detection as described previously …”
Section: Methodsmentioning
confidence: 99%
“…For patients on TDF shown to harbor the rtN236T mutation by population sequencing, the rtN236T mutant percentage was determined with MultiCode RTx allele-specific PCR modified for HBV rtN236T detection as described previously. 21 Adherence to Study Medication. For patients qualifying for genotypic analysis, adherence was assessed by evaluation of plasma tenofovir levels (liquid chromatography/mass spectroscopy) and by analysis of drug accountability records associated with case report forms or included in clinical deviation logs.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that due to a high error rate during replication of HBV DNA, these variants may have emerged spontaneously and may not have been acquired at the time of infection. Although we found a higher prevalence of HBV‐DR variants by NGS, the clinical significance of these variants present as a minor species is unclear, and most studies reported no impact of these minor variants on response to NUC therapy . Of the eight participants with DR variants detected by NGS who subsequently started NUC therapy, five had primary DR variants detected by NGS but none by Sanger sequencing.…”
Section: Discussionmentioning
confidence: 53%